Systematic Literature Review terhadap Efektivitas Firewall MikroTik dalam Mitigasi Serangan Jaringan - Muhammad Najin; Rachel Ajerna Cecilia Gerungan; Yustian Servanda (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
cyberattacks, including Distributed Denial of Service (DDoS), brute-force attacks, flooding, and unauthorized access, may result in financial losses, data breaches, service disruptions, and damage to network infrastructure. Numerous studies have investigated the implementation of MikroTik firewalls using different methods, configurations, and case studies, resulting in varying levels of effectiveness. However, no systematic review has comprehensively summarized the effectiveness of MikroTik firewall implementations based on different attack types and firewall configurations. This study aims to analyze, compare, and evaluate the effectiveness of MikroTik firewalls in mitigating network attacks using a Systematic Literature Review (SLR) approach. The study adopted the PRISMA guidelines through the stages of identification, screening, eligibility assessment, and article selection based on predefined inclusion and exclusion criteria. Furthermore, the selected articles were analyzed using a comparative synthesis approach to identify implementation patterns, attack types, and the effectiveness of the firewall methods employed. The findings indicate that Firewall Filter Rules are the most frequently implemented method in MikroTik firewalls, whereas Firewall RAW provides better performance in mitigating high-traffic attacks such as DoS, DDoS, and Ping Attack. In addition, firewall effectiveness is influenced by the applied configuration, attack characteristics, and the hardware capacity of the router.